Evaluating deep learning models for sentiment classification - Karakus, Betul Ay; Talo, Muhammed; Hallac, Ibrahim Riza; Aydin, Galip (Wiley, 2018)
Deep learning has emerged as an effective solution to various text mining problems such as document classification and clustering, document summarization, web mining, and sentiment analysis. In this paper, we describe our work on investigating several deep learning models for a binary sentiment classification problem. We used movie reviews in Turkish from the website to train and test the deep learning models. We also report a detailed comparison of the models in terms of accuracy and time performances. Two major deep learning architectures used in this study are Convolutional Neural Networks and Long Short-Term Memory. We built several variants of these models by changing the number of layers, tuning the hyper-parameters, and combining models. Additionally, word embeddings were created by applying the word2vec algorithm with a skip-gram model on a large dataset (approximate to 13M words) composed of movie reviews. We investigate the effect of using the pre-word embeddings with these models. Experimental results have shown that the use of word embeddings with deep neural networks effectively yields performance improvements in terms of run time and accuracy.
5th Turkish High Performance Computing Conference (BASARIM) -- SEP 14-15, 2017 -- Istanbul, TURKEY
Keywords: big data; CNN; deep learning; LSTM; sentiment classification; word embeddings